Analisis Aktivitas Matematika Pada Permainan Domino Di SMP MHI Bangsalsari Jember - Novia Indah Sari; Dwi Novi Sulisawati; Marsidi Marsidi (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2026)
Domino is a game that contains various mathematical elements and has the potential to be utilized as a contextual learning medium. This study aims to describe the forms of mathematical activities that emerge during domino games and to analyze their contribution to mathematics learning. This research employed a qualitative method with a descriptive approach. The research subjects consisted of two students from SMP MHI Bangsalsari Jember who were 15 years old, had the highest mathematics achievement, and had prior experience playing domino. Data were collected through observation, semi-structured interviews, and documentation. Data analysis was conducted through data collection, data reduction, data presentation, and conclusion drawing, supported by source triangulation to ensure data validity. The findings revealed that seven mathematical activities emerged during the domino game, namely classifying, counting, determining position or location, arranging and recognizing patterns, enumerating, estimating, and explaining. Both subjects demonstrated involvement in all indicators of mathematical activities, although at different levels of depth. Subject YE exhibited more analytical, strategic, and systematic thinking skills, whereas subject NA tended to apply a more practical and situational approach. The results indicate that domino games can serve as a learning medium that naturally promotes mathematical activities and supports the development of students' mathematical thinking skills. Therefore, domino games have the potential to be used as an alternative mathematics learning medium that is contextual, engaging, and meaningful. Keywords: Mathematical Activities, Domino Game